Reach of “VAMOS” program in basic healthcare - organizational barriers and facilitators - Borges,Rossana Arruda (2019)
Abstract Objective : To investigate the organizational barriers and facilitators to the reach of the “Active Life Health Improvement Program” (or VAMOS) implemented in two Basic Health Units (BHU) in Santa Catarina, Brazil. Method : An experimental study was carried out, based on the RE-AIM framework (http://www.re-aim.org/). Barriers and facilitators were identified through a focus group, semi-structured interview and content analysis. Results : In terms of reach, of the 297 Basic Health Care (BHC) users from the two BHU, 51 elderly people participated, a rate of 17.2%. One notable barrier identified was the lack of support from health teams, while the recommendation of the program by health professionals was found to be a facilitator. Conclusion : The VAMOS program has the potential to be incorporated as a public policy in the process of health care and promotion in BHC. It is an unprecedented strategy in Brazil, aimed at behavioral change, using a sustainable system, the BHU, which has a considerable population reach.